If it's not what You are looking for type in the equation solver your own equation and let us solve it.
36=8(y-6)+4y
We move all terms to the left:
36-(8(y-6)+4y)=0
We calculate terms in parentheses: -(8(y-6)+4y), so:We get rid of parentheses
8(y-6)+4y
We add all the numbers together, and all the variables
4y+8(y-6)
We multiply parentheses
4y+8y-48
We add all the numbers together, and all the variables
12y-48
Back to the equation:
-(12y-48)
-12y+48+36=0
We add all the numbers together, and all the variables
-12y+84=0
We move all terms containing y to the left, all other terms to the right
-12y=-84
y=-84/-12
y=+7
| w=16÷4 | | 180=4x+132 | | v^{2}=361 | | –4+7w=6w | | j+17=16 | | X=40,y= | | 5r-6=5(r-1) | | 3w+26=5(w+8) | | 60+9x=-2+10x | | 10q=–8+9q | | 5x+5=380 | | 5x+0.5=7x-0.05 | | 8x-30=192 | | 2y+6+5y=27 | | -10-3x=-6(x+8)-4 | | 4=x/23 | | −5/2x+9=3x-2 | | a/7/8=60/100 | | 22y-7=7/2y-85/2 | | 2(3x-1)-2x=4(x+2)-3 | | 511x+23x−16x=−189 | | 1x=4x+12 | | 2x-10+9=14x-10-12x | | 2=x-17 | | 45+25x=120 | | 89÷37=15r2 | | h-5=7.2 | | 87=83⋅8x | | 32x-15=0 | | 14x^2+63x=0 | | 12x-16=7x-8 | | y=-4/5=-2/5 |